Economic Development and Institutions - Véronique Dutraive (Revue de la Régulation)
This paper offers an overview and an inquiry into what I will call the New New Institutional Economics (NNIE). D. North’s analysis and transition experiments are considered as major sources of this research program. The implications of this NNIE for the development policies recommended or requested by international organizations are also discussed.